The occurrence of the carbapenemase gene, blaNDM-5, on a transmissible IncX3 plasmid in multidrug-resistant Escherichia coli isolated from a farm dog - Dina Daaboul; Issmat I. Kassem; Khaled El Omari; Fouad Dabboussi; Saoussen Oueslati; Thierry Naas; Marwan Osman (Journal of Global Antimicrobial Resistance, 2024)
ABSTRACT: Objectives: In-depth phenotypic and genomic analyses on a carbapenem-resistant Escherichia coli isolate, recovered from the faeces of a farm dog in Lebanon, focusing on its antimicrobial resistance (AMR) patterns and the underlying resistome. Methods: E. coli strain EC-106 was identified using MALDI-TOF-MS. Analyses using Carba NP, immunochromatographic assay NG Carba5, and other antimicrobial susceptibility testing were performed. Whole-genome sequencing (WGS) using the Illumina technology and different software available at the Center of Genomic Epidemiology wwere used to predict the resistome, sequence type (ST), plasmid types, and virulence genes. Results: Susceptibility testing revealed that E. coli EC-106 was multi-drug resistant, including against newer antimicrobials such as imipenem-relebactam (MIC = 16 µg/mL), meropenem-vaborbactam (MIC = 16 µg/mL), and ceftazidime-avibactam (MIC > 32 µg/mL), but remained susceptible to aztreonam (MIC = 0.12 µg/mL), aztreonam-avibactam (MIC = 0.06 µg/mL), and cefiderocol (MIC = 0.5 µg/mL). WGS analyses showed that E. coli EC-106 carried 13 acquired resistance genes associated with resistance to β-lactams (blaNDM-5 and blaTEM-1B), aminoglycosides (aac(3)-IId, aph(3′)-Ia, aadA1, and aadA2), tetracyclines (tetA), amphenicols (partial catA1), macrolides (mphA), sulphonamides (sul1 and sul3), trimethoprim (dfrA12), and quaternary ammonium compounds (partial qacE). The blaNDM-5 was located on an IncX3 plasmid. The isolate was predicted to be a human pathogen (92.9%) and belonged to ST1011. Conclusion: To our knowledge, this is the first report of the detection of an IncX3 plasmid carrying the blaNDM-5 gene in animals in Lebanon, highlighting the severe AMR challenges in the country. Taken together, our current and previous findings suggest that blaNDM-5 might be spreading in different hosts and genetic backgrounds across clinical and non-clinical settings.